162k views
5 votes
4(2q – 3) = 8q-12

Pls solve and show steps

2 Answers

3 votes


4(2q - 3) = 8q - 12


8q - 12 = 8q - 12


8q + - 12 = 8q + - 12


- 12 - 8q = - 12 - 8q


- 12 = - 12


- 12 + 12 = - 12 + 12


0 = 0

By the above equation , we can conclude that any real number can be placed in the place of q to make the left hand side of the equation become equal to the right hand side of the equation .

Therefore , any real number ( integer , fraction and rational number ) can be placed in the place of q .

User Bopjesvla
by
4.9k points
2 votes

Answer:

LHS = RHS = -12

Explanation:

=> 4(2q - 3 ) = 8q - 12.

=> 8q - 12 = 8q - 12 .

=> 8q - 8q - 12 = -12 .

=> -12 = -12 .

Hence LHS = RHS .

User Yisu
by
5.3k points